DEER-Stitch: combining three- and four-pulse DEER measurements for high sensitivity, deadtime free data. - Lovett, J; Lovett, B; Harmer, J (2012)
Over approximately the last 15 years the electron paramagnetic resonance (EPR) technique of double electron electron resonance (DEER) has attracted considerable attention since it allows for the precise measurement of the dipole-dipole coupling between radicals and thus can lead to distance information between pairs of radicals separated by up to ca. 8 nm. The "deadtime free" 4-pulse DEER sequence is widely used but can suffer from poor sensitivity if the electron spin-echo decays too quickly to allow collection of a sufficiently long time trace. In this paper we present a method which takes advantage of the much greater sensitivity that the 3-pulse sequence offers over the 4-pulse sequence since the measured electron spin-echo intensity (for equal sequence lengths) is greater. By combining 3- and 4-pulse DEER time traces using a method coined DEER-Stitch (DEERS) accurate dipole-dipole coupling measurements can be made which combine the sensitivity of the 3-pulse DEER sequence with the deadtime free advantage of the 4-pulse DEER sequence. To develop the DEER-Stitch method three systems were measured: a semi-rigid bis-nitroxide labeled nanowire, the bis-nitroxide labeled protein CD55 with a distance between labels of almost 8 nm and a dimeric copper amine oxidase from Arthrobacter globiformis (AGAO).